Video interaktif mandarin corner untuk keterampilan menyimak Bahasa Mandarin - Kurniawati, Novia; Afifah, Lilis; Fefi Laksana SaktI, Karina (2020)
The purpose of this study is to describe the application of Mandarin Corner interactive video media to practice the listening skill of class X MAN 1 Probolinggo students and to describe students' responses to the application of the media. This study used descriptive qualitative method. The data source of this study were 24 students at MAN 1 Probolinggo language class. The data were collected using the observation sheets and the interview guidelines. The results of the observations show that the application of the Mandarin Corner interactive video carried out in accordance with the learning plan went smoothly and received good responses from all students, although there were obstacles that researchers experienced when implementing this video. These constraints are because of learning is done online, researcher could directly monitor students activities and the learning process run longer than targeted. Based on the result of student interviews it is known that with Mandarin Corner video media students can more easily understand the material, the learning process becomes interesting and not boring, and makes them more enthusiastic to learn Mandarin